A bigger house at the cost of an empty fridge? The effect of households' indebtedness on their consumption: Micro-evidence using Belgian HFCS data - Philip Du Caju; Guillaume Périlleux; François Rycx; Ilan Tojerow (National Bank of Belgium, 2021)
This paper investigates the potentially non-linear relation between households' indebtedness and their consumption between 2010 and 2014 in Belgium. To do so, we use panel data from the two waves of the Household Finance and Consumption Survey. Unlike previous studies, we find a negative effect of households' indebtedness on their consumption, even in the absence of any negative shock on their assets. Our findings suggest that, without such a shock, it is the day-to-day sustainability of the debt, rather than its overall sustainability, that leads households to reduce their consumption. To explore potential non-linearities in this effect, we perform a threshold analysis, whose results suggest that households should not have a debt-service-to-income ratio greater than 30% as this leads to a substantial reduction of their consumption. The effect appears to be robust to various specifications, including the inclusion of other European countries, to result from a trade-off between housing and consumption, and to be more prevalent among more fragile households.
Keywords: D12; D14; E21; 330; Households; Indebtedness; Consumption; Debt-Service-to-Income; Non-linear Heterogeneous Effects